Outcomes of Endoscopic Management among Patients with Bile Leak of Various Etiologies at a Tertiary Care Center - Suprabhat Giri; Sridhar Sundaram; Harish Darak; Sanjay Kumar; Shobna Bhatia (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Bile leak is a common complication of cholecystectomy, and it is also observed in other conditions such as ruptured liver abscess, hydatid cyst, and trauma. Endoscopic retrograde cholangiopancreatography (ERCP) is the first-line management for such conditions. However, studies on the outcomes of endoscopic management for bile leaks with etiologies other than post-cholecystectomy injury are extremely limited. Methods We conducted a retrospective review of patients with symptomatic bile leak who were referred to a tertiary care center and who underwent ERCP between April 2016 and April 2019. The primary outcome was complete symptomatic resolution without extravasation of the contrast medium during the second ERCP conducted after 6 weeks. Results In total, 71 patients presented with symptomatic bile leak. The etiologies of bile leak were post-cholecystectomy injury in 34 (47.8%), liver abscess in 20 (28.1%), and post-hydatid cyst surgery in 11 (15.4%) patients. All patients were managed with ERCP, sphincterotomy, and stent placement for 6 weeks, except for one who underwent surgery. The primary outcome was achieved in 65 (91.5%) of 71 patients. There was no significant difference in terms of outcome in relation to the interval between the diagnosis of bile leak and ERCP. Conclusions Most patients with bile leak can be successfully managed with ERCP even when performed on an elective basis.